Pengaruh Kualitas Produk, Content Marketing, Customer Engagement, dan Harga terhadap Keputusan Pembelian UMKM Zisallection - Tertia, Nandinani Siti; Devanny, Indira; Afifah, Raulia Bunga; Meliana, Vina (STREAMING, 2022)
This study aims to determine the effect of product quality, content marketing, customer engagement and price on purchasing decisions of MSMEs Zisallection in Jabodetabek. This study uses quantitative methods and nonprobability sampling technique with purposive sampling method. The sample used 230 female respondents who had bought and followed Zisallection on Instagram. The analyzing technique of this research includes validity test, reliability test, classical assumption test, and hypothesis testing. The results showed that product quality has an effect on purchasing decisions, content marketing has an effect on purchasing decisions, customer engagement has an effect on purchasing decisions, and price has an effect on purchasing decisions. Product quality, content marketing, customer engagement, and price simultaneously effect on purchasing decisions.